2021
DOI: 10.15376/biores.16.2.hubbe
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of polyelectrolyte complexes and ionic bonding to performance of barrier films for packaging: A review

Abstract: Barrier films that are used on packages play an important role, especially in the protection of food products. Research is being carried out at an accelerating pace to replace petroleum-based plastic films, which do not biodegrade and are difficult to recycle. This review article considers publications related to the use of polyelectrolyte complexes (PECs) in barrier films as a strategy to decrease the permeation of oxygen and other substances into and out from packages. Research progress has been achieved in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 203 publications
0
6
0
Order By: Relevance
“…41 The improvement in OGR as well as the water/moisture barrier properties of paperboards enabled by ball-milled complex dispersion coating could possibly be ascribed to the high degree of the electrostatically crosslinked polymer network, uniform film formation, and tailored polarity, leading to a notably reduced free volume, high cohesive energy density, and reduced hydrophilicity. 14 We compare grease resistance and improvement in moisture barrier properties of our best-performing complex dispersion coating with previously reported natural or functionalized biopolymeric coatings (Figure 7a and Table S5). Due to the extensive hydrogen-bonding network, most natural biopolymers, such as cellulose nanofibrils (CNFs) or nanocrystals (CNCs), starch, and caseinate, generally show a certain level of grease resistance.…”
Section: ■ Results and Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…41 The improvement in OGR as well as the water/moisture barrier properties of paperboards enabled by ball-milled complex dispersion coating could possibly be ascribed to the high degree of the electrostatically crosslinked polymer network, uniform film formation, and tailored polarity, leading to a notably reduced free volume, high cohesive energy density, and reduced hydrophilicity. 14 We compare grease resistance and improvement in moisture barrier properties of our best-performing complex dispersion coating with previously reported natural or functionalized biopolymeric coatings (Figure 7a and Table S5). Due to the extensive hydrogen-bonding network, most natural biopolymers, such as cellulose nanofibrils (CNFs) or nanocrystals (CNCs), starch, and caseinate, generally show a certain level of grease resistance.…”
Section: ■ Results and Discussionmentioning
confidence: 96%
“…Diffusion coefficient, determined by the free volume and the degree of mobility of polymer chains, and the solubility of a gas molecule in barrier coating, influenced by coating material chemistry, polarity, and structure (such as crystallinity and degree of crosslinking), are two key factors to block the diffusive transport of gases . The improvement in OGR as well as the water/moisture barrier properties of paperboards enabled by ball-milled complex dispersion coating could possibly be ascribed to the high degree of the electrostatically crosslinked polymer network, uniform film formation, and tailored polarity, leading to a notably reduced free volume, high cohesive energy density, and reduced hydrophilicity …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When observing the coverage of the two-layer barrier-coated paper depending on the NFC type, the two-layer barrier-coated paper using cationic and anionic NFCs showed better coverage than that using only anionic NFCs. According to the ionic bonding mechanism described by Hubbe (2021), it has been reported that bonds formed with opposite-charged ionic groups can improve barrier properties of film in comparison to a default system. This prior study supports the finding that the opposite-charged coating exhibited higher coating weight and Gurley air permeability value in comparison to like-charged coating due to electrostatic attraction by different ionic properties.…”
Section: Characteristics Of the Two Nfcsmentioning
confidence: 99%
“…The properties of PECs are influenced by factors such as pH, ionic strength, and the structure of the polyelectrolytes. 7 Unlike covalent cross-linking, PECs are formed through reversible ionic associations, eliminating the need for toxic cross-linkers. This characteristic makes PECs advantageous for various applications in the food and biomedical fields.…”
Section: ■ Introductionmentioning
confidence: 99%